1987
DOI: 10.1097/00000658-198711000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Insertion and Management of Complications

Abstract: In a series of 602 procedures, over 90% of primary forearm insertions of PTFE grafts between the radial artery and a cubital vein were possible. Thrombosis of the graft, which was invariably due to venous outflow obstruction, was the most common complication encountered. Revision of the venous anastomosis was not necessary in about one-third of the thrombosed grafts if a size 3 coronary dilator could be passed and the augmentation test was satisfactory. For revisions, creation of a new venous anastomosis using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
6

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(60 citation statements)
references
References 5 publications
2
52
0
6
Order By: Relevance
“…The PGE has been evaluated in many single-centre studies and good results have been reported in 74-80% (ref. 37,53,81,82,89 ). Although, this approach is not generally accepted.…”
Section: Graft Infection Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The PGE has been evaluated in many single-centre studies and good results have been reported in 74-80% (ref. 37,53,81,82,89 ). Although, this approach is not generally accepted.…”
Section: Graft Infection Therapymentioning
confidence: 99%
“…In patients with arteriovenous graft the incidence of infection is from 11 to 35% (ref. 13,[32][33][34][35] ), and infection complications associated with arteriovenous graft are approximately one third more than arteriovenous fistula 23 . Also later published studies have shown that the incidence of infection in arteriovenous graft is ten times more common than autologous fistula and significantly lower than central venous catheter 13,36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] In this case, traumatic fi stula between a vascular access graft and the adjacent basilic vein formed by repeated needling for maintenance HD likely was the predisposing factor in the graft thrombosis. Presently, and consistent with the typical scenario, blood fl ow in the venous limb of the graft was decreased due to steal through the traumatic fi stula.…”
Section: Discussionmentioning
confidence: 76%
“…The major predisposing factor for thrombosis of PTFE grafts is stenosis of the graft-venous anastomosis. [7][8][9] But, factors other than venous stenosis may also cause or contribute to graft thrombosis. Prosthetic arteriovenous graft thrombosis is multifactorial and includes stenosis of the graft-venous and graft-arterial anastomosis, excessive compression for hemostasis at the end of dialysis, complication of dialysis needle placement, hypotension, hypovolemia, and hypercoagulable states.…”
Section: Discussionmentioning
confidence: 99%